The Theory of the Top. Volume I Introduction to the Kinematics and Kinetics of the Top - Klein, Felix; Sommerfeld, Arnold (Birkhäuser Boston : Imprint: Birkhäuser, 2008)
The Theory of the Top: Volume I. Introduction to the Kinematics and Kinetics of the Top is the first of a series of four self-contained English translations of the classic and definitive treatment of rigid body motion. Key features: * Complete and unabridged presentation with recent advances and additional notes * Annotations by the translators provide insights into the nature of science and mathematics in the late 19th century * Each volume interweaves theory and applications Volume I focuses on providing fundamental background material and basic theoretical concepts. The Theory of the Top was originally presented by Felix Klein as an 1895 lecture at Göttingen University that was broadened in scope and clarified as a result of collaboration with Arnold Sommerfeld. Graduate students and researchers interested in theoretical and applied mechanics will find this a thorough and insightful account. Other volumes in this series include Development of the Theory for the Heavy Symmetric Top, Perturbations: Astronomical and Geophysical Applications, and Technical Applications of the Theory of the Top.